Perspectives of Biogas Conversion into Bio-CNG for Automobile Fuel in Bangladesh. (30th August 2017) - Shah, M. S.; Halder, P. K.; Shamsuzzaman, A. S. M.; Hossain, M. S.; Pal, S. K.; Sarker, E.
Abstract : The need for liquid and gaseous fuel for transportation application is growing very fast. This high consumption trend causes swift exhaustion of fossil fuel reserve as well as severe environment pollution. Biogas can be converted into various renewable automobile fuels such as bio-CNG, syngas, gasoline, and liquefied biogas. However, bio-CNG, a compressed biogas with high methane content, can be a promising candidate as vehicle fuel in replacement of conventional fuel to resolve this problem. This paper presents an overview of available liquid and gaseous fuel commonly used as transportation fuel in Bangladesh. The paper also illustrates the potential of bio-CNG conversion from biogas in Bangladesh. It is estimated that, in the fiscal year 2012-2013, the country had about 7.6775 billion m 3 biogas potential equivalent to 5.088 billion m 3 of bio-CNG. Bio-CNG is competitive to the conventional automobile fuels in terms of its properties, economy, and emission.